1969
DOI: 10.1002/neu.480010206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of micro‐iontophoretic administration of magnesium and calcium on neurones in the central nervous system of cats

Abstract: SUMMARYCa2 + and Mg2 + released from five-barrelled micropipettes by currents of 5 to 80 nA caused a deceleration of the firing rate of neurones discharging spontaneously, or excited by the simultaneous administration of glutamate or acetylcholine, in the cerebral cortex, cuneate nucleus and spinal cord. Excitation of cells in the cuneate nucleus, caused by stimulation of sense organs, was also suppressed by Ca2+ and Mgz+. Synaptic transmission of volleys, evoked by electrical stimulation, from thalamus to cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1969
1969
1981
1981

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The intensity of this depression varied greatly with different cells: it was usually more pronounced than the depressant effect of ACh (as in Fig. 3B-C), but less so than that of Ca2+ or Mg2+ (Kato & Somjen, 1969).…”
Section: Effects Of Ba2+mentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity of this depression varied greatly with different cells: it was usually more pronounced than the depressant effect of ACh (as in Fig. 3B-C), but less so than that of Ca2+ or Mg2+ (Kato & Somjen, 1969).…”
Section: Effects Of Ba2+mentioning
confidence: 99%
“…A higher threshold is thus the predominant feature of the action of Ca2+ and Mg2+ on most types of excitable tissue (Shanes, 1958;Cerf, 1963), including cortical neurones (Krnjevic 1965;Kato & Somjen, 1969;Kelly et at. 1969).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial experiments, double-barrelled micropipettes were used, one barrel containing 3 M-KC1 and the other 0-2 m-CaCl2 (according to previous experience (Kato & Somjen, 1969), this concentration is more satisfactory for microiontophoresis than 0 5 or 1 M). However, it soon became evident that substantial injections of Cat' were necessary and that any effect produced might not greatly outlast the period of injection.…”
Section: Introductionmentioning
confidence: 99%
“…This effect of Ca on transmitter release occurs also at synapses of frog motoneurones (Katz & Miledi, 1963;Grinnell, 1966). On the other G. E. DAMBACH AND S. D. ERULKAR hand, Krnjevi6 (1965), Kato & Somjen (1969) and Kelly, Krnjevid & Somjen (1969) have shown that Ca ions have a direct depressant action on the electrical excitability of neurones in the cerebral cortex as well as in other parts of the central nervous system, but they were unable to record any increase in transmitter release by the Ca. Thus, two separate effects of Ca on central neurones have been described: one effect on transmitter release and the other on neural excitability.…”
Section: Introductionmentioning
confidence: 99%